The sum of the three terms of a geometric progression is 14. If the first two terms are each increased by one and the third decreased by one, the resulting numbers are in arithmetic progression . Find the value of the biggest term.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes, with a r = 4 we have that
a + a r + a r 2 = 1 4 ⟹ r 4 + 4 + 4 r = 1 4
⟹ r 2 + 2 r = 5 ⟹ 2 r 2 − 5 r + 2 = 0
⟹ ( 2 r − 1 ) ( r − 2 ) = 0 ⟹ r = 2 1 or r = 2 .
With r = 2 1 the GP is 8 , 4 , 2 and the AP 9 , 5 , 1 .
The terms of the geometric progression are a 1 , a 2 and a 3 . We let the terms of the arithmetic progression be x 1 , x 2 and x 3 . Based form the problem,
x 1 = a 1 + 1
x 2 = a 2 + 1
x 3 = a 3 − 1
We know that the common difference in an arithmeric progression is equal. So
x 2 − x 1 = x 3 − x 2
Substituting, we have
a 2 + 1 − ( a 1 + 1 ) = a 3 − 1 − ( a 2 + 1 )
a 2 + 1 − a 1 − 1 = a 3 − 1 − a 2 − 1
a 2 − a 1 = a 3 − a 2 − 2
2 a 2 + 2 = a 1 + a 3 (equation 1)
From here, we are stuck in our solution, but in the problem it says that the sum of the geometric progression is 1 4 , so we can use that information.
a 1 + a 2 + a 3 = 1 4
a 1 + a 3 = 1 4 − a 2 (equation 2)
We now equate the two equations.
a 1 + a 3 = a 1 + a 3
2 a 2 + 2 = 1 4 − a 2
3 a 2 = 1 2
a 2 = 4
Now our problem is a 1 and a 3 , we know the the common ratio in a geometric progession is equal. So
a 1 a 2 = a 2 a 3
a 1 4 = 4 a 3
Cross multiply !
1 6 = ( a 1 ) ( a 3 ) (equation 3)
From equation 2,
a 1 + a 3 = 1 4 − a 2
a 1 + a 3 = 1 4 − 4
a 1 = 1 0 − a 3 , substitute this to equation 3, we have
1 6 = ( a 1 ) ( a 3 )
1 6 = ( 1 0 − a 3 ) ( a 3 )
( a 3 ) 2 − 1 0 a 3 + 1 6 = 0
By factoring, we obtain
a 3 = 8 or a 3 = 2 , but a 3 must be larger that a 2 ! so a 3 is 8 .
Problem Loading...
Note Loading...
Set Loading...
let the terms be a, ar, ar^2 then a + ar + ar^2 = 14 .....(1) (ar + 1) - (a + 1) = (ar^2 - 1) - (ar + 1) ar + 1 - a - 1 = ar^2 - 1 - ar - 1 ar^2 - 2ar + a = 2 .......(2) (1) - (2) 3ar = 12 ar = 4 it follows that a = 2, ar = 4, ar^2 = 8 => r 2 or 1/2 the biggest term is 8.